Correlation between inflammatory markers and impaired circadian clock gene expression in type 2 diabetes mellitus. (October 2019) - Yu, Rongguo; Tian, Linlin; Ding, Yi; Gao, Yali; Li, Daiqing; Tang, Yunzhao
Highlights: Clock genes of peripheral blood cells is impaired in type 2 diabetes (DT2). Inflammatory markers are associated with circadian clock gene expression in DT2. HbA1c levels were negatively correlated with CLOCK genes. Abstract: Aim: Circadian rhythm controls a wide variety of physiological processes in the body. Disruption of the circadian clock in metabolic tissues may increase the risk of diabetes, obesity, and metabolic syndrome. The following study investigated whether the expression of clock genes of peripheral blood cells is impaired in type 2 diabetes (DT2) and whether inflammatory markers are associated with circadian clock gene expression in DT2 patients. Materials and methods: Blood samples were obtained from 36 DT2 patients and 14 non-diabetic volunteers. Transcript levels of circadian clock genes were analyzed using real-time quantitative PCR; plasma inflammatory markers were measured by ELISA or clinical laboratory test. Results: The CLOCK, BMAL1, PER1, CRY1 and CRY2 mRNA levels were decreased in the diabetic patients. In addition, HbA1c levels were negatively correlated with BMAL1, PER1 and CRY1 mRNA levels. The levels of IL-6, TNF-α and CRP were higher in diabetic subjects compared to control subjects. Impaired expression of circadian clock gene was interrelated with the elevated levels of plasma IL-6 and TNF. Moreover, a multiple linear regression showed that plasma IL-6 level was correlated with impaired expression of circadian clock gene. Conclusions: Circadian clock genes are reduced in peripheral leucocytes of DT2 patients. Furthermore, impaired expression of circadian clock gene are interrelated with the elevated levels of plasma inflammatory markers.